A flowsheet model for the development of a continuous process for pharmaceutical tablets: An industrial perspective. Issue 2 (25th September 2017) - García‐Muñoz, Salvador; Butterbaugh, Adam; Leavesley, Ian; Manley, Leo Francis; Slade, David; Bermingham, Sean
Abstract : A dynamic model of a continuous direct compression process for pharmaceutical tablets is presented. The objective is to assess the impact of the variability from the feeder system on the concentration of drug in the powder in the feed frame of a tablet press. The model is based on principles of dispersed flow from the reaction engineering field. An estimability analysis was performed to understand the impact of the available measurements on the estimated parameters and suggest better ways to approach the parametrization. Predictions are successfully contrasted with experimental data. The model is used to produce residence time distributions at different process conditions and a graphical representation of the allowable range of disturbances in the feeders that can be mitigated by the process. The model was used in support of the method development for an online near infrared sensor. © 2017 American Institute of Chemical Engineers AIChE J, 64: 511–525, 2018